Strategic manufacturing for competitive advantage : a CSIR & HLL symposium - Ganguly, Ashok S. (Ashok Sekhar), 1935-; Chadha, P. K. (Prem K.); Lahiri, A.; Dhanuka, V. R. (Oxford & IBH Pub. Co., 1998)
Proceedings of a seminar jointly organized by the Council of Scientific & Industrial Research (India) and Hindustan Lever Limited in Bangalore on 12th Mar. 1997.